Bitcoin İle Finansal Makro Değişkenler Arasındaki İlişki: Türkiye Üzerine Bir Var Analizi - İşcan, Hüseyin (Muş Alparslan Üniversitesi, 2020)
The aim of this study, the relations between Bitcoin, exchange rate, Stock Exchange Istanbul index and interest rate variables are to examine using weekly data for the period 2013:11-2019:10 for Turkey. In the study, by establishing a VAR model, long-term and causality relationships between variables were investigated, and analysis was concluded with effect-response graphs and variance decomposition table. As a result of the study, there was no long-term correlation and causation relationship between Bitcoin and other variables; however, causation relations between the other variables were determined. According to the impact-response charts, the exchange rate reacted negatively to a shock to Bitcoin for three weeks, and the response in other weeks was meaningless. It is seen that there is on crypto coins in Turkey a certain awareness, but this awareness there is not in long-term investment dimension and there is not strong enough to affect macro variables. It needs some time to spread the technology, which can be considered new in Turkey.

Bu çalışmada amaç; Bitcoin, döviz kuru, Borsa İstanbul Endeksi ve faiz değişkenleri arasındaki ilişkileri Türkiye için 2013:11-2019:10 dönemi haftalık verileri kullanarak incelemektir. Çalışmada VAR modeli kurularak değişkenler arasındaki uzun dönem ve nedensellik ilişkileri araştırılmış, etki-tepki grafikleri ve varyans ayrışım tablosuyla analiz sonuçlandırılmıştır. Çalışma sonucunda Bitcoin ile diğer değişkenler arasında uzun dönemde herhangi bir eşbütünleşme ilişkisi ve nedensellik ilişkisi tespit edilememiş, ancak diğer değişkenlerin kendi aralarında nedensellik ilişkileri saptanmıştır. Etki-tepki grafiklerine göre Bitcoin’e verilen bir şoka döviz kuru üç haftalık negatif tepki göstermiş diğer haftalarda verilen tepki anlamsız olmuştur. Türkiye’de kripto paralar üzerinde belirli bir farkındalığın olduğu ancak bu farkındalığın uzun vadeli yatırım boyutunda ve makro değişkenleri etkileyebilecek güçte olmadığı görülmektedir. Türkiye’de yeni sayılabilecek olan bu teknolojinin yaygınlaşabilmesi için belirli bir zamana ihtiyaç vardır.
The Relationship Between Bitcoin and Financial Macro Variables: a Var Analysis on Turkey
anemon
Keywords: Bitcoin; Exchange rate; Borsa İstanbul Index; Interest rate; Bitcoin; Döviz kuru; Borsa İstanbul Endeksi; Faiz Oranı